Autoreactive T-Lymphocytes in Inflammatory Skin Diseases - Boehncke, Wolf-Henning; Brembilla, Nicolo Costantino (Frontiers in Immunology, 2019)
The presence of one or several autoantigen(s) and a response by the adaptive immune system are the key criteria to classify a pathology as an autoimmune disease. The list of entities fulfilling this criterion is currently growing in the light of recent advancements in the pathogenetic understanding of a number of important dermatoses. The role of autoreactive T-lymphocytes differs amongst these pathologies. While they are directly involved as effector cells attacking and sometimes killing their respective target in some diseases (e.g. vitiligo), they provide help to B-lymphocytes, which in turn produce the pathogenic autoreactive antibodies in others (pemphigus and pemphigoid). Atopic dermatits is a chimera in this regard, as there is evidence for both functions. Psoriasis is an example for an entity where autoantigens were finally identified, suggesting that at least a subgroup of patients should be classified as suffering from a true autoimmune rather than autoinflammatory condition. Identification of resident memory T-lymphocytes (TRM) helped to understand why certain diseases relapse at the same site after seemingly effective therapy. Therefore, the in-depth characterization of autoreactive T-lyphocytes goes way beyond an academic exercise and opens the door towards improved therapies yielding durable responses. TRM are particularly suitable targets in this regard, and the clinical efficacy of some established and emerging therapeutic strategies such as the inhibition of Janus Kinase 3 or interleukin 15 may rely on their capacity to prevent TRM differentiation and maintenance. Research in this field brings us closer to the ultimate goal in the management of autoimmunity at large, namely resetting the immune system in order to restore the state of tolerance.